Targeted Combined Endpoint Improvement in Patient and Disease Domains in Atopic Dermatitis: A Treat-to-Target Analysis of Adults with Moderate-to-Severe Atopic Dermatitis Treated with Upadacitinib - Shawn G. Kwatra; Marjolein de Bruin-Weller; Jonathan I. Silverberg; Peter Lio; Mette Deleuran; Handan Aydin; Brian M. Calimlim; Michael C. Lane; Yingyi Liu; Sarah Ofori; Stephan Weidinger (Medical Journals Sweden, 2024)
A treat-to-target approach was recently developed to guide systemic treatment for adults with atopic dermatitis (AD). Recommendations outlined criteria for a 3-month initial acceptable treatment target and a 6-month optimal target, evaluated using global assessment of patient-reported disease severity, as well as Eczema Area and Severity Index, itch assessed on an 11-point numerical rating scale, Dermatology Life Quality Index, or Patient-Oriented Eczema Measure. Achievement of these targets with once-daily upadacitinib (15 mg and 30 mg) monotherapy was evaluated using integrated adult data from the Measure Up 1 and 2 phase 3 studies. Among the 852 patients treated with upadacitinib 15 mg or 30 mg, the 3-month initial acceptable target was achieved by >80%, >78%, and ≥87% of patients, and the 6-month optimal target was achieved by ≥53%, >61%, and >73% of patients at weeks 2, 16, and 52, respectively. Achievement of all 6 individual criteria for each of the target goals also increased over time. These findings suggest that upadacitinib 15 mg and 30 mg may help improve standards of care in patients with moderate-to-severe AD by achieving 6-month target goals at 16 weeks and as early as 2 weeks for most patients.